2017
DOI: 10.7448/ias.20.01.21796
|View full text |Cite
|
Sign up to set email alerts
|

New HIV testing technologies in the context of a concentrated epidemic and evolving HIV prevention: qualitative research on HIV self‐testing among men who have sex with men and transgender women in Yangon, Myanmar

Abstract: Introduction: Global effort to increase early diagnosis and engagement in HIV care emphasize the importance of developing novel approaches to reaching those missed by traditional methods. Such needs are particularly great for men who have sex with men (MSM), transgender women (TW), and other populations who face stigma. Myanmar’s HIV epidemic is concentrated among key populations and the revised National Strategy aims to reduce late diagnosis and barriers to care to curb HIV incidence among these groups. HIV s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 25 publications
(25 reference statements)
5
47
0
1
Order By: Relevance
“…HIVST provides individuals with an accurate, convenient test that can assure privacy and confidentiality, overcoming traditional barriers to facility-based testing among key populations [12,16,17]. Available studies from Asia, have shown HIVST to be acceptable among MSM and TGW [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…HIVST provides individuals with an accurate, convenient test that can assure privacy and confidentiality, overcoming traditional barriers to facility-based testing among key populations [12,16,17]. Available studies from Asia, have shown HIVST to be acceptable among MSM and TGW [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…2 Global efforts to address the HIV epidemic emphasize improving access to HIV testing, particularly among key populations. 3 HIV testing barriers that trans women experience include stigma, discrimination, and marginalization. 4,5 Members of this population in Lebanon experience these barriers due in part to rigid expectations of binary gender expression, 6 which can hinder HIV testing, early detection, and linkage to care.…”
Section: Introductionmentioning
confidence: 99%
“…The HIVST has been put forward as a strategy to extend HIV diagnoses that may contribute to the reduction of transmission by enabling early diagnosis, access to care and treatment, and reduced viral load [20,39,40]. Our results suggest that the acceptability of HIVST is higher precisely among those who have already tested for HIV, and thus justify ample promotion of HIVST, particularly to MSM who are not used to routine testing.…”
Section: Discussionmentioning
confidence: 82%